2021
DOI: 10.3390/jcm10081712
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients with Multiple Intracranial Aneurysms after Subarachnoid Hemorrhage and Future Risk of Rupture of Unruptured Aneurysm

Abstract: The purpose was to study the risk of rupture of unruptured intracranial aneurysms (UIAs) of patients with multiple intracranial aneurysms after subarachnoid hemorrhage (SAH), in a long-term follow-up study, from variables known at baseline. Future rupture risk was compared in relation to outcome after SAH. The series consists of 131 patients with 166 UIAs and 2854 person-years of follow-up between diagnosis of UIA and its rupture, death or the last follow-up contact. These were diagnosed before 1979, when UIAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Andic et al [ 16 ] believed that one-stage MIA treatment with combined endovascular techniques was technically feasible but that its safety due to relatively high complication rates remained controversial (i.e., because unruptured tiny aneurysms weighted the low annual spontaneous rupture rate and potential surgical risks) [ 17 ]. A long-term follow-up study [ 18 ] revealed that patients with moderate or severe disability after SAH have a relatively low risk of UIA rupture. Furthermore, over shorter follow-up, intervention and observation appear similarly safe for bystander aneurysms in MIAs [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Andic et al [ 16 ] believed that one-stage MIA treatment with combined endovascular techniques was technically feasible but that its safety due to relatively high complication rates remained controversial (i.e., because unruptured tiny aneurysms weighted the low annual spontaneous rupture rate and potential surgical risks) [ 17 ]. A long-term follow-up study [ 18 ] revealed that patients with moderate or severe disability after SAH have a relatively low risk of UIA rupture. Furthermore, over shorter follow-up, intervention and observation appear similarly safe for bystander aneurysms in MIAs [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AComA complex is a prevalent site for UIAs, constituting up to 33% of cases. A number of studies underscore its elevated risk of rupture, as indicated by a meta-analysis reporting a 2.51 times higher risk for AComA aneurysms compared to those in other anterior circulation sites [15,16]. Moreover, small AComA UIAs have been reported to bear a similar risk of rupture to posterior circulation aneurysms [17].…”
Section: Discussionmentioning
confidence: 99%
“…The anterior communicating artery (AComA) region stands out from other anatomical locations due to its congestion of functionally important structures, namely, numerous perforators, and relatively frequent prevalence of AComA UIAs. Additionally, AComA UIAs may exhibit twice the risk of rupture than other UIAs with an annual risk of rupture as high as 2.2% [2,3].…”
Section: Introductionmentioning
confidence: 99%